2007
DOI: 10.1002/anie.200700269
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric Detection of Mercuric Ion (Hg2+) in Aqueous Media using DNA‐Functionalized Gold Nanoparticles

Abstract: Color is everything: Hg2+ in aqueous media is detected by the formation of thymidine–Hg2+–thymidine coordination complexes, which raises the melting temperature of the DNA‐hybridized gold nanoparticle probes and thus the temperature at which the probes disperse and effect a purple‐to‐red color change. The method has very high sensitivity and selectivity, and it provides a simple and fast colorimetric readout (see picture).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
718
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,223 publications
(728 citation statements)
references
References 98 publications
7
718
1
2
Order By: Relevance
“…Various metal ions were detected by monitoring the color changes occurring upon aggregation of ligand-functionalized AuNPs through specific molecular interactions [26][27][28][29][30]. However, studies on colorimetric anion recognition and sensing anions by AuNPs are limited [31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Various metal ions were detected by monitoring the color changes occurring upon aggregation of ligand-functionalized AuNPs through specific molecular interactions [26][27][28][29][30]. However, studies on colorimetric anion recognition and sensing anions by AuNPs are limited [31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…[25,26] To manage the mercury contamination problem, many sensors have been developed. [27] In particular, a large number of fluorescent, [15,[28][29][30] colorimetric, [31,32] and electrochemical sensors [33,34] have been designed based on the Hg II -thymine binding. In the original paper by Ono et al, [15] the DNA shown in Figure 1A was labeled with a 6-carboxyfluorescein (FAM) and a dark quencher (4-(4-dimethylaminophenyl) diazenylbenzoic acid, Dabcyl), respectively on the two ends.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] While this interaction is highly specific for Hg 2+ , it is strongly influenced by buffer conditions such as pH, temperature, ionic strength, and anion species, 16,17 making it difficult for detection in real sample matrix. Another strategy relies on RNA-cleaving DNAzymes.…”
Section: Introductionmentioning
confidence: 99%